Enhancing Choice and Outcomes for Therapeutic Trials in Chronic Pain: N-of-1 + Imaging (+ i). (February 2020) - Borsook, David; Upadhyay, Jaymin; Hargreaves, Richard; Wager, Tor
Abstract : The attrition of novel analgesic drugs in the clinic can be attributed in the main to two factors: failure of preclinical research findings translating into human pain conditions, and a drop-off of efficacy between proof-of-concept (i.e., Phase II trials) and pivotal, confirmatory (Phase III trials) testing. In order to enhance the efficiency of the clinical drug evaluation process and determine rapidly whether a potential therapeutic candidate gives pain relief, by modulating central pain neurobiology, we propose a 'pre-proof-of-concept' approach, in which an efficacy assessment is performed in a single individual (N-of-1) using subjective clinical pain assessments supported by objective validated functional neuroimaging measures. Using an N-of-1 + i methodology, clinical- and neuroimaging-based metrics can be quantified under conditions of drug versus placebo or drug versus current standard of care conditions. Highlights: N-of-1 trials have been useful in a number of clinical conditions, most notably, cancer. For analgesics, it may be an optimal manner to enhance drug trials to evaluate new clinical entities. Biomarker development is critical to improved evaluation of therapeutic candidates. Advances in neuroimaging (e.g., pharmaco-magnetic resonance imaging; brain measures of structure and function) as a potential biomarker allow for objective measures of drug effects and brain responses to be added to N-of-1 trials (N-of-1 + i). Combining these two approaches will enhance specificity (because of repeated measures, limiting placebo response, etc.) and selectivity of choice of treatments, as well as enable multiple potential indications to be evaluated in early Phase II trials. A better understanding of the utility of N-of-1 + i may facilitate a transformation in drug trial innovation (innovative trial design) and personalized medicine.